PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, INSENTIF, BUDAYA ORGANISASI TERHADAP KEPUASAN KERJA PEGAWAI (STUDI PADA BAPPEDA KOTA MATARAM) - Johan Mustafa Kamal (Master of Management, Mataram University, 2017)
This research is aimed at 1) determining the effect of transformasional leadership of satisfactory of employees of Bappeda (Planning and Regional Development Agency) of Mataram, 2) determining the effect of incentiveon the work satisfactory of employees of Bappeda of Mataram, 3) determining the effect of organizational culture on the work satisfactory of employees of Bappeda of Mataram. The population of this research ware all employees of Bappeda of Mataram. The sample of the research ware 39 employees selected through census method. The data ware collected through questionnaires, documentation, and interview. The data were examine with multiplee linear regression using SPSS program. The reasearch showed that the were of transformasional leadership, incentive, and organizational culture had positive effect of the work satisfactory of employees of Bappeda of Mataram.Keyword:transformasional leadership,, incentive,organizational culture, work satisfactory